Measurement on radiation shielding parameters of FexCr1_x and FexNix alloys - Turşucu, Ahmet; Elmahroug, Youssef; Yılmaz, Demet (Springer Science and Business Media Deutschland GmbH, 2021)
In this present work, the gamma-ray radiation shielding parameters of nine different FexCr1-x. and FexNix alloys that were prepared at different mixture rates have been investigated. The gamma-ray shielding has different parameters which are total mass attenuation coefficient (µt), effective atomic number (Zeff) and effective electron density (Neff), half-value layer (HVL), tenth value layer (TVL), exposure buildup factor (EBF), energy absorption buildup factor (EABF) components. These shielding parameters have been measured experimentally by using gamma photons in the energy range from 0.0175 MeV to 0.05954 MeV. WinXCOM, ParShield and Phy-X program results were compared with values from experimental measurements used in characterizing the radiation shielding properties. The experimental mass attenuation coefficient values are in good concordance with the WinXCOM evaluations, with ranging from 0.04 to 13.21%. Also, the mass attenuation coefficient values derived using the ParShield and Phy-X simulations program have compared with WinXCOM. These values are quite agreed with the WinXCOM values. Additionally, in this work, the radiation shielding parameters are calculated by using experimental values and deviated values of theoretical calculations of WinXCOM, ParShield and Phy-X. It has been determined that the theoretical calculation programs are quite compatible. While some of the experimental radiation absorption findings almost exactly overlapped with the WinXCOM values, it was observed that there were acceptable differences with the ParShield and Phy-X values.
Keywords: Buildup factors; HVL; Mass attenuation coefficient; TVL